Nabi Musa Menampar Malaikat Maut: Jalan Tengah Polemik Hadis Musykil - Izzuddin Washil; Ahmad Khoirul Fata (Pascasarjana IAIN Sultan Amai Gorontalo, 2019)
Hadith which tells the story of the Prophet Musa slapping the angel of death invites polemic among the scholars. There is a group that can accept it with various explanations, there are also those who consider death is unacceptable even though the sanad is valid. Therefore this hadith is included as an improbable hadith. This paper tries to find a way out of the polemic. In this discussion, the author can accept opinions that reject this Hadith if the flow of understanding can be accounted for. However, the author can also accept opinions that accept it if the flow of understanding can be accounted for. An important part that must be revealed immediately in this hadith is the certainty whether or not Moses knew that what came to him was the grim reaper. If an explanation of this has been obtained, of course, we are easier to determine the attitude of accepting or rejecting this hadith. But certainty is difficult to obtain because the text of this hadith does not explicitly inform it. So what must be done now is tawaqquf.